Persepsi Remaja Terhadap Kesan Menakutkan Pada Peringatan Kesehatan Bergambar Di Bungkus Rokok Ditinjau Dari Extended Parallel Process Model - Rahmawati, Andi Annisa Dwi; Damayanti, Rita; Anshari, Dien (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2018)
Background. Pictorial Health Warnings (PHWs) on cigarette packs are intended to prevent teenagers from smoking. However, little is known on how teenage smokers perceive the scary images on PHWs. Objective. To explore how fear appeal strategy progresses to the acceptance or rejection of the messages among teenage smokers who had completed a smoking cessation program and among those who never join such program. Method. This qualitative study used the Rapid Assessment Procedures (RAP) design, collecting data through in-depth interviews with 12 teenage smokers from one public and one private high schools. Results. Participants who received intervention had higher self-confidence to reduce cigarette consumption and to quit smoking easily than those who did not receive the intervention. Those who received the intervention also showed a good acceptance of the messages in PHWs as reflected in their positive attitude and higher intention to quit smoking. Participants who did not receive the intervention showed rejection of the messages because they could not control the fear that aroused and prefer to avoid seeing the PHWs.